Dalaw - Aquino, Kris; Ocampo, Diether; Pareno, Gina
"Stella (Kris Aquino) decides to marry Anton (Diether Ocampo), three years after her husband died. Anton was her great love before she was forced by her parents to marry Danilo. However, after the wedding, she experiences major hauntings that endanger her life and the people around her. All the clues are pointing to her dead husband. Feeling guilty of her ex-husband's death, Stella tries to save her family from the ghost's wrath. Along the way, secrets start to unravel and Stella is now unsure of who's haunting her and why is she being haunted."